2001
DOI: 10.1055/s-0037-1616059
|View full text |Cite
|
Sign up to set email alerts
|

Anti-β2 Glycoprotein I Antibodies Cause Inflammation and Recruit Dendritic Cells in Platelet Clearance

Abstract: SummaryScavenger phagocytes are mostly responsible for the in vivo clearance of activated or senescent platelets. In contrast to other particulate substrates, the phagocytosis of platelets does not incite pro-inflammatory responses in vivo. This study assessed the contribution of macrophages and dendritic cells (DCs) to the clearance of activated platelets. Furthermore, we verified whether antibodies against the β2 Glycoprotein I (β2GPI), which bind to activated platelets, influence the phenomenon. DCs did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Interestingly, the treatment was effective at inducing the development of anti‐β 2 GPI antibodies in both autoimmune‐prone and normal mice (Figure 4). Further experiments will be necessary to verify whether other particulate substrates that expose phosphatidylserine (63, 64) are an equally efficient source of β 2 GPI for crosspresentation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the treatment was effective at inducing the development of anti‐β 2 GPI antibodies in both autoimmune‐prone and normal mice (Figure 4). Further experiments will be necessary to verify whether other particulate substrates that expose phosphatidylserine (63, 64) are an equally efficient source of β 2 GPI for crosspresentation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…27 Results were expressed as the percentage of annexin A5 ϩ events in the whole CD61 ϩ platelet For personal use only. on May 12, 2018. by guest www.bloodjournal.org From population.…”
Section: Activation Of Platelets and Neutrophilsmentioning
confidence: 99%
“…27 Results were expressed as the percentage of annexin A5 ϩ events in the whole CD61 ϩ platelet population. To determine P-selectin expression, platelets were simultaneously fixed (Thrombofix 18 ), labeled with FITC-conjugated mAb against CD61 and PE-conjugated against P-selectin, and analyzed by flow cytometry in purified platelet suspensions as well as in whole-blood samples.…”
Section: Activation Of Platelets and Neutrophilsmentioning
confidence: 99%
“…By analysing the proteins that associate with the liposomes in blood, Chonn et al identified β2-glycoprotein I as a major protein associated with rapidly cleared liposomes and noted that pretreating the mice with anti-β2-glycoprotein I antibodies significantly increased the half-life of the liposomes (26). In vitro, β2-glycoprotein I was also shown to promote the phagocytosis of phosphatidylserine containing liposomes, activated platelets (8,27,28) and apoptotic tumour cells (29). In conditions associated with increased microvesicles generation such as disseminated intravascular coagulation, plasma levels of β2-glycoprotein I was reduced presumably due to its consumption (30).…”
Section: Discussionmentioning
confidence: 99%